2007
DOI: 10.1111/j.1346-8138.2007.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness and patient satisfaction for treatment with low‐dose cyclosporin administration in patients with moderate psoriasis vulgaris

Abstract: The Japanese guidelines for psoriasis therapy with cyclosporin microemulsion preconcentrate (CyA MEPC) has been revised, and the clinical application of CyA MEPC is being expanded to include mild to moderate psoriasis. In this study, we aimed to confirm the clinical efficiency of low-dose cyclosporin therapy in patients with moderate psoriasis vulgaris. After informed consent was obtained, 19 patients with psoriasis vulgaris were enrolled in this study. Each patient basically administrated CyA MEPC, 2.5 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Eight grade A2 studies [116, 118, 121, 124, 163–165, 172], nine grade B studies [130, 133, 136, 166, 168, 173–176], and three grade C studies [177–179] were included on combination therapy with vitamin D and other topical or systemic therapies. A general distinction may be made between topical combination therapy, combination drugs (i.e., different active ingredients in one preparation), and sequential combinations of different preparations (i.e., agents in two different preparations).…”
Section: Topical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Eight grade A2 studies [116, 118, 121, 124, 163–165, 172], nine grade B studies [130, 133, 136, 166, 168, 173–176], and three grade C studies [177–179] were included on combination therapy with vitamin D and other topical or systemic therapies. A general distinction may be made between topical combination therapy, combination drugs (i.e., different active ingredients in one preparation), and sequential combinations of different preparations (i.e., agents in two different preparations).…”
Section: Topical Therapymentioning
confidence: 99%
“…The resulting evidence level was 1. In regard to combination therapy, seven grade A 2 studies [260], three grade B studies [173, 262, 267], and three grade C studies [177, 268, 269], were included.…”
Section: Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…6 In our previous study, almost all patients whose initial PASI score ranged 12-18 showed a significant improvement and 75% clearance of PASI score within 12 weeks by CyA MEPC administration. 9 Thus, a new strategy can be raised; an intermittent CyA MEPC administration combined with topical vitamin D3 application for patients in the aggressive phase. 9,10 We propose the term "supplementary therapy" for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although surveys indicate that patients may frequently remain under ineffective treatment for longer than necessary [7,14,15,16], only few studies have analysed patient satisfaction with health care provision in psoriasis [17,18,19,20]. In the Multinational Assessment of Psoriasis and Psoriatic Arthritis (MAPP) study, van de Kerkhof et al [12] showed that approximately 40% of dermatologists were comfortable, but conservative, in their use of biologic therapy.…”
Section: Introductionmentioning
confidence: 99%